Economic evaluation of thermal power station investments considering the impact of renewable energy sources - Adelino J. C. Pereira (2012)
With the advent of power system restructuring, there is now competition on the generation activity and the generation mix changed in many countries with the incentives to induce investments in renewables, in many cases, using volatile primary resources. Given this increase of the installed capacity in wind parks and PV stations as well as in hydro stations (as a way to address the mentioned volatility), investments in large thermal stations became more risky. In this scope, this paper describes a long term generation expansion planning model that can be used by generation companies to investigate the profitability of new thermal generation investments considering the increasing presence of renewables. This long term simulation tool uses System Dynamics, a framework particularly suited to mode the long term dependencies between different variables while incorporating delays on some decisions. At a final section this paper includes a Case Study based on a generation system that corresponds to a scaled version of the Portuguese system.